Loaded colon causing death: A case report - Cyriac, Sebin K; Ratheesh, P T (Journal of Indian Academy of Forensic Medicine, 2021)
Colon can be loaded with faecal matter following acute or chronic constipation. Most of the time it can be relieved with medical or  surgical interventions. Rarely does it produce complications due to perforation by impacted stool causing peritonitis and sepsis. Here  we came across the case of a young female who is brought dead to casualty following vomiting and abdominal pain. The medico legal  autopsy showed a hugely dilated colon loaded with faecal matter causing respiratory and cardiovascular compromise due to the  pressure effect on thoracic structures. The cause for the constipation in this case was an imperforated anus at birth which was operated  in childhood itself but was not cured completely. We could hardly get this kind of complication with faecal impaction from literature  as there are very few reported cases.
Keywords: Loaded colon; Faecal impaction; Chronic constipation; Imperforate anus; Respiratory distress